Perbandingan Otago, Basic Exercise, dan Kombinasi Keduanya Terhadap Kekuatan Otot dan Fungsional Berjalan Penderita Osteoarthritis - Dian Ambarwaty Prasetyo; Andi Ariyandy; Irfan Idris (Politeknik Negeri Jember, 2022)
Osteoarthritis (OA) is the most common joint disease that reduces quality of life. It’s often associated with impaired mobility due to pain and muscle weakness, thus being a risk factor for falls down. This study aimed to compare the effect of otago exercise, basic exercise, and a combinations of the two on changes in muscle strenght and functional ability to walk in patients with knee OA. This study was a comparative analytic study with 60 participants divided into three treatments. There were a total of 20 paticipants in each treatment. Repeated ANOVA was used as a statistical test with significancy p ≤ 0,05. The result, there was a significant difference between the three treatment groups in term of changes in muscle strength (p=0.003) and functional ability to wal (p=0.036). Post hoc results showed that the combined otago exercise and basic exercise group had a significantly difference in muscle strength and fungsional ability to walk than the otago exercise and basic exercise group. This study concludes that combining otago exercise and basic exercise is more efective than otago exercise or basic exercise only in increasing muscle strenght and functional ability to walk.